0369 Effect of Lemborexant on Sleep Architecture in Older Adults with Insomnia Disorder. (12th April 2019) - Moline, Margaret; Murphy, Patricia; Pinner, Kate; Cheng, Jocelyn; Perdomo, Carlos; Kumar, Dinesh; Zammit, Gary; Mayleben, David
Abstract: Introduction: Insomnia is characterized by changes in sleep-wake architecture, including reduction and temporal redistribution of N3 and REM sleep. For older adults, insomnia may exacerbate normal age-related changes in sleep-wake architecture. Current insomnia treatments may decrease wake after sleep onset but suppress N3 and/or REM sleep. Polysomnography data from SUNRISE-1, a Phase 3 clinical study in older (≥ 55y) adults with insomnia disorder, were examined to assess the effect of lemborexant (LEM) on sleep architecture. Methods: SUNRISE-1 (NCT02783729) was a global, randomized, placebo (PBO)- and active-controlled (zolpidem tartrate extended release 6.25mg [ZOL]) 30 day study. Subjects were randomized to nightly PBO, ZOL, LEM 5mg (LEM5) or LEM 10mg (LEM10). Sleep architecture was assessed by polysomnography at baseline during a single blind placebo run-in, and during the first two (N1/2) and last two (N29/30) nights of treatment. Mean values for each sleep stage were based on 2 consecutive nights of PSG recordings. Results: SUNRISE-1 randomized 1006 subjects (208 PBO, 263 ZOL, 266 LEM5, 269 LEM10), 86.4% female, 72.3% white, median age 63.0 years. Demographic and baseline characteristics, including PSG, were similar across treatment groups. Compared with PBO, LEM5 and LEM10 significantly increased N2, NREM, REM, and total sleep time (TST) at N1/2 and N29/30 (all p<0.0001), N1 only at N29/30 (p<0.0001), and for LEM 5, N3 at N1/2 (P<0.05). Compared with ZOL, LEM5 and LEM10 significantly increased N1, REM, and TST at N1/2 and N29/30, NREM at N29/30, and for LEM5, N2 at N1/2 (all p<0.05). REM latency was significantly reduced for LEM5 and LEM10 compared to PBO and ZOL at N1/2 and N29/30 (all p<0.0001). The reduction in REML was less by N29/30 than N1/2. Conclusion: In older adults with insomnia, LEM treatment results in improvement of sleep architecture, with increased time in all stages and reduction of REML compared with PBO, and was superior to ZOL for most measures. These results suggest that LEM may ameliorate the alterations of sleep architecture in older insomnia patients. Support (If Any): Eisai, Inc., Purdue Pharma, L.P.